Ambulatory 24-h intraocular pressure monitoring in the management of glaucoma. Issue 3 (May 2015) - Mansouri, Kaweh; Weinreb, Robert N.
<x xml:space="preserve">Abstract</x> Purpose of review To review current status and future of ambulatory 24-h intraocular pressure monitoring. Despite important advances in the diagnosis and management of glaucoma during the last decade, the fundamental understanding of intraocular pressure, its only modifiable risk factor, remains elusive. The current practice of single intraocular pressure measurements during a clinic visit does not adequately reflect the variability of intraocular pressure throughout the 24-h day. Recent findings There has been considerable progress recently with the prototype and commercial introduction of continuous 24-h intraocular pressure monitoring devices. Implantable intraocular pressure sensors have the advantage to directly measure intraocular pressure over many months and years, whereas temporary (contact lens based) approaches provide a noninvasive alternative for repeated 24-h periods. This review provides an overview of implantable devices as well as a critical assessment of a 24-h contact lens sensor. Summary Recent advances in microelectromechanical systems and nanoelectromechanical systems have enabled the development of 24-h intraocular pressure monitoring devices. Once these technologies have shown their safety and efficacy, larger questions as to the data interpretation and handling will arise. It is likely that the use of 24-h intraocular pressure monitoring will herald fundamental changes in our understanding and management of glaucoma.